2012
DOI: 10.1139/g11-073
|View full text |Cite
|
Sign up to set email alerts
|

Detection of interstitial telomeric sequences in the Arctic charr (Salvelinus alpinus) (Teleostei: Salmonidae)

Abstract: Highly polymorphic Arctic charr ( Salvelinus alpinus Linnaeus, 1758) chromosomes were studied using conventional and molecular methods. The diploid chromosome number in the studied individuals was 2n = 81 or 2n = 82, with a fundamental arm number (NF) = 100. These differences are due to Robertsonian fusions. Interindividual variation in the number and size of DAPI and CMA(3) positively stained chromatin sites was observed in studied specimens. In the case of two individuals, the subtelomeric region of the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Individuals from the brook trout broodstock are characterized by a diploid chromosome number (2n) and a chromosome arm number, FN (Fundamental Number), which are 84 and 100, respectively (Ocalewicz et al 2004). In the Arctic char individuals from Rutki broodstock, diploid chromosome number varies from 81 to 82 (FN = 100) (Pomianowski et al 2012). Brook trout eggs collected from four females were inseminated with the spermatozoa from one Arctic char male.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals from the brook trout broodstock are characterized by a diploid chromosome number (2n) and a chromosome arm number, FN (Fundamental Number), which are 84 and 100, respectively (Ocalewicz et al 2004). In the Arctic char individuals from Rutki broodstock, diploid chromosome number varies from 81 to 82 (FN = 100) (Pomianowski et al 2012). Brook trout eggs collected from four females were inseminated with the spermatozoa from one Arctic char male.…”
Section: Methodsmentioning
confidence: 99%
“…Other mechanisms leading to the ITS formation have been suggested in three Salvelinus species: lake trout (Salvelinus namaycush), brook trout (Salvelinus fontinalis) and the Arctic charr (Salvelinus alpinus) showing subterminal position of the interstitial telomeric sequences (Figure 1c-d) assigned to the vicinity of the CMA 3 positive GC-rich heterochromatin (Reed and Phillips, 1995;Ocalewicz et al, 2004b;Pomianowski et al, 2012). Guanine-rich chromosomal regions are involved in several rearrangements like transpositions, duplications and (or) translocations resulted in multichromosomal location and variation in size of CMA 3 positively stained chromatin in Salvelinus species (Phillips et al, 1988;Phillips and Ráb, 2001).…”
Section: Itss and Minor Rearrangements -A Salvelinus Fish Casementioning
confidence: 97%
“…In the case of the Arctic char metaphase spreads showing extended chromatin, the non-telomeric fluorescent hybridization signal covered a longer stretch of the chromosome than the signal from the telomere position, however the interstitial signal was less intense. This observation suggested that telomeric regions and ITS might have different structures (Pomianowski et al, 2012). It is possible that telomeric DNA sequences were not the only component of the ITS region.…”
Section: Itss and Minor Rearrangements -A Salvelinus Fish Casementioning
confidence: 98%
See 2 more Smart Citations